Morphological studies of Cimex lectularius Linnaeus, 1758 (Hemiptera: Cimicidae) - Kawasima, Elton Shinti [UNESP]; Paiva, Vinicius Fernandes de; Belintani, Tiago; Justino, Hernany Henrique Garcia [UNESP]; Nascimento, Juliana Damieli; Pinotti, Heloisa [UNESP]; Oliveira, Jader de; Rosa, Joao Aristeu da [UNESP] (Soc Chilena Entomologia, 2022)
In the family Cimicidae, the genus Cimex stands out for its importance in public health. These hemipterans are known as bed bugs and their presence generally indicates poor hygiene and poverty. Cimex lectularius is a hematophagous insect and has a global distribution. In Brazil, control occurs indirectly, due to the control of other vectors. The real knowledge of the epidemiological situation is still compromised by under-reporting. To contribute to the knowledge of the biology and taxonomy of these hematophagous insects, the morphological characters of adults and the five nymphal instars of C. lectularius were analyzed and characterized by means of scanning electron microscopy (SEM). Morphological study by SEM allowed the characterization of eggshell, each nymphal instar, the sexual differentiation of fifth instar nymphs, female, and male external genitalia. In this study it was possible to evaluate the morphological characters of C. lectularius, of all five nymphs' instars. It is relevant to characterize the morphology of these insects, since the results obtained can contribute to the control actions, as well as to the taxonomic studies of this species.
Keywords: Bed bugs; external genitalia; nymphal instar; taxonomy